Guidance on how to develop complex interventions to improve health and healthcare. Issue 8 (12th August 2019) - O'Cathain, Alicia; Croot, Liz; Duncan, Edward; Rousseau, Nikki; Sworn, Katie; Turner, Katrina M; Yardley, Lucy; Hoddinott, Pat
Abstract : Objective: To provide researchers with guidance on actions to take during intervention development. Summary of key points: Based on a consensus exercise informed by reviews and qualitative interviews, we present key principles and actions for consideration when developing interventions to improve health. These include seeing intervention development as a dynamic iterative process, involving stakeholders, reviewing published research evidence, drawing on existing theories, articulating programme theory, undertaking primary data collection, understanding context, paying attention to future implementation in the real world and designing and refining an intervention using iterative cycles of development with stakeholder input throughout. Conclusion: Researchers should consider each action by addressing its relevance to a specific intervention in a specific context, both at the start and throughout the development process.